2015
DOI: 10.1097/igc.0000000000000382
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Recurrent Uterine Papillary Serous Carcinoma Treated With Platinum-Based Chemotherapy

Abstract: Platinum-based CT is an active regimen in recurrent UPSC even if patients received prior adjuvant platinum CT. Platinum-free interval predicts response and outcome of platinum-based CT in recurrent setting such as in ovarian cancer. Plantinum-taxane is more active than platinum-gemcitabine in recurrent UPSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…All patients in our study were subjected to surgical staging. Due to the fact that non-endometrioid tumors have a worse prognosis, all patients, including those in the early stages, should receive adjuvant treatment [22]. However, the efficacy of postoperative adjuvant chemotherapy in these patients remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…All patients in our study were subjected to surgical staging. Due to the fact that non-endometrioid tumors have a worse prognosis, all patients, including those in the early stages, should receive adjuvant treatment [22]. However, the efficacy of postoperative adjuvant chemotherapy in these patients remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most common management strategy for USC is hysterectomy and surgical staging, followed by platinum/paclitaxel-based chemotherapy and radiation therapy [ 3 , 4 , 5 , 6 , 7 ]. However, most USC patients have an unfavorable 5-year survival rate (41%) and poor outcomes due to high recurrence rates and limited effective treatment for recurrence [ 8 , 9 , 10 , 11 ]. Thus, new therapeutic strategies to manage USC are needed.…”
Section: Introductionmentioning
confidence: 99%
“…UPSC is histologically indistinguishable from high‐grade serous ovarian carcinoma. UPSC tends to have high risk of recurrence and lower survival after recurrence . Prior studies, showed similarities in response to platinum based chemotherapy and applicability of platinum free interval between recurrent UPSC and serous ovarian carcinoma .…”
Section: Introductionmentioning
confidence: 98%